România rurală și integrarea europeană - Petre, Ioana (Calitatea Vieții, 2007)
This study compares two types of population: on the one hand, the Romanians and, particulary, the rural population, and on the other hand, European people resulting from the other 25 countries which have joined the European Union before Romania. The object of this comparison was the positive or negative attitudes regarding the European project. We may say that there is, at least, one thing that makes the difference between these two types of people: Romanian population, including the rural one, is much more optimistic about the benefits brought out by the European integration than Europeans resulting from the other 25 countries. We may also say that some social categories, like peasants, unskilled workers, unemployed or old people have the same reaction to the benefits of European Union: there is no such thing for themselves. So, they are, beyond the country of origin, against integration; they prefer rather to reject the European project than to approve’it.